RANCANG BANGUN SISTEM WEB PADA PROTOTYPE STASIUN PENGISIAN KENDARAAN LISTRIK - Agustadewa, Yosia; Rahardjo, Pratolo; Duta Nugraha, I Putu Elba (Program Studi Teknik Elektro UNUD, 2024)
In 2023, sales of electric cars in Indonesia experienced a significant increase, reaching 10,327 units when compared to sales in 2021. The existence of electric vehicles requires supporting facilities for the existence of electric vehicles called charging stations. So that users can charge their electric vehicles, a system is needed that can control and monitor the charging of electric vehicles via the web. Web design using Next.js framework on the frontend and Go language on the backend. The web can start charging, stop charging, and display charging data graphs in real time. Web system testing on prototype charging station using BlackBox testing method and obtained eight valid test items.